LA LEXICOGRAFÍA CARIBEÑA COMO SÍMBOLO DE LA IDENTIDAD LINGÜÍSTICA Y CULTURAL DE UN PUEBLO - Allsopp, Jeannette (2012)
This articles discusses the very important theme of Caribbean lexicography as the chronicle which symbolizes what we refer to as the linguistic and cultural identity of the Caribbean people, exemplified in Caribbean reference works. Its two main objectives are first of all, to sensitize the Caribbean people to the fact that there are linguistic and cultural similarities between the territories and secondly, to illustrate through examples of ítems taken from regional lexicography that there is undoubtedly one single Caribbean identity. In order to achieve this, the article clarifies what is meant by the concept linguistic and cultural identity, by placing it within a theoretical framework and relating it to the specific material presented. The article also seeks to explain what is meant by “Caribbean lexicography”, thereby demonstrating its role in uniting a multilingual and multicultural región through its recording of the language, culture, ecology, dishes, religión, folklore and the general way of life of the Caribbean people, and illustrates the fact that Caribbean nations, although separated by the Caribbean Sea, are definitely one people.